Present and future of subthalamotomy in the management of Parkinson´s disease: a systematic review. (4th May 2021) - Máñez-Miró, Jorge U.; Rodríguez-Rojas, Rafael; Del Álamo, Marta; Martínez-Fernández, R.; Obeso, José A.
ABSTRACT: Introduction: The subthalamic nucleus (STN) is known to be involved in the pathophysiology of Parkinson´s disease and by reducing its abnormal activity, normal output of basal ganglia can be restored along with improvement in PD cardinal motor features. Deep brain stimulation of the STN is currently the main surgical procedure for PD with motor complications, but lesioning can be an alternative. Areas covered: Here, the authors systematically review the current evidence regarding subthalamotomy both with radiofrequency and, more recently, with focused ultrasound (FUS) for the treatment of PD. Expert opinion: Unilateral subthalamotomy for the treatment of PD motor features can be considered a viable option in asymmetric patients, particularly with FUS which allows a minimally invasive safe and effective ablation of the STN. Risk of inducing dyskinesia (i.e., hemichorea/ballism) may be strikingly reduced when lesions enlarge dorsally to impinge on pallidothalamic fibers.